PEMANFAATAN LIMBAH PENGOLAHAN BAUKSIT UNTUK PEMBUATAN AGREGAT BUATAN - Hariyani, Susi; Asmadi, Asmadi (Jurusan Teknik Sipil Polnep, 2020)
This filling material for concrete is known as aggregate which usually uses stone as the base material. This stone material will eventually run out, so new innovations are needed to replace it. The purpose of this study was to determine the physical and mechanical properties of concrete made using artificial aggregate mixture where the aggregate material is made by utilizing bauxite processing waste. Artificial aggregates are made to replace gravel as a filler. The waste is treated with 2 treatments, namely added with kaolin and without kaolin, and then burned. Concrete specimens are made in a cylindrical shape with a height of 30 cm with a diameter of 15 cm, with variations in artificial aggregate with the addition of kaolin and without the addition of kaolin with the aggregate substitution of 10%, 20% and 30% then evaluated physical properties such as weight content and absorption of concrete and the concrete mechanic is in the form of the compressive strength of the concrete. According to SNI 03 6468 2000, the quality of concrete produced from concrete mixtures using artificial aggregate from bauxite waste is classified as low compressive strength concrete (low strength concrete). with fc '<20 MPa and according to SNI 03-2847-2002, concrete produced by mixing artificial aggregate is categorized as lightweight concrete, with a unit weight of <1.900 kg / m³